Integrasi Islamic Renewable Fund dan Green Islamic Note untuk Microgrid Hijau Berbasis Ekonomi Syariah - Zahira Al-Ghifari; Aisyah Adifa Azzahidah; Nazwa Zaliaputri; Alendra Nauval Mufti Rayhan (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2026)
The global energy crisis and rising carbon emissions caused by the continued dependence on fossil fuels have become major challenges to sustainable development, including in Indonesia. In the higher education sector, the implementation of renewable energy through the green campus concept still faces significant obstacles, particularly limited green financing, low participation of academic communities, and the lack of integration between Islamic economics and renewable energy technology. Nevertheless, universities possess a strategic role as centers of innovation and education capable of fostering a younger generation that supports the transition toward a sustainable Islamic green economy. This research employs a normative-juridical method using conceptual and qualitative-descriptive approaches with a normative-conceptual orientation through library research on regulations, Islamic economic theories, green finance, and renewable energy concepts. The study aims to formulate an innovative, participatory, and sustainable sharia-based financing model to support the development of green microgrids within university environments through the integration of the Islamic Renewable Fund (IRF) and Green Islamic Note (GIN). The findings reveal that GIN functions as a community-based Islamic green financing instrument that enables students, lecturers, alumni, and the broader academic community to participate as investors in renewable energy projects through a digital, transparent, and sharia-compliant mechanism. In addition to serving as a micro-investment scheme based on mudharabah and musyarakah principles, GIN also acts as an experiential learning platform that strengthens students’ green skills, Islamic financial literacy, leadership capacity, and ecological awareness. Therefore, the integration of IRF and GIN has the potential to establish energy-independent and environmentally sustainable campuses while simultaneously advancing Islamic economic development in the era of global energy transition.